The Impact of Contract Strategy on Achievement and Retention of Female Fourth Intermediate Students Class in the Subject of Arab-Islamic History Civilization - Wadi, Hiba Hameed; Saeed, Wijdan Jassim Mohammed; Fadhel, Sahar Hussein; Rasheed, Mujahid HAMEED (International Journal of Psychosocial Rehabilitation, 2020)
The world today progresses enormously in the field of knowledge and generate ideas to address the attitudes of life in the present and the future, and is not new a n cumulative knowledge and composition of the hierarchical base of prior knowledge, which is based on what is new interacting with her, and this vast amount of knowledge has grown need to reach the best ways And facilitate it to surround that knowledge and to be able to organize and interact with it to face the requirements of life that increase and get complicated with the progress and complexity of life. And that education need humanitarian supplies the individual and society actors by force that you pay for further scientific progress and it is a reflection of the needs and aspiration of society kept her scientific development in the various field of education to review the plans, goals and methods of learning and teaching. Modern education calls for making the learner the center of the educational process and focusing on his activity, uniqueness and differences, and considering that learning has a personality trait, and it takes place within the individual in highly personal and clear ways, and is unique in terms of the results, timing and process associated with it. Although it is not no way a particular represent the best ways to teach all subjects, but there are strategies and teaching methods directly play the teacher 's central role to control the process education in terms of planning, implementation and follow - up as the teacher has a learner in which participants a high proportion in the educational process is encouraged and motivated Emphasis on the focus and attention in this type of learning , and teaching learners self- reliance behaviors and to instill a spirit of competition, cooperation and proper adaptation, whether with himself or with the environment in which he lives